2022
DOI: 10.3201/eid2806.212262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Healthcare-Associated and Community-Associated Clostridioides difficile Infections among Adults, Canada, 2015–2019

Abstract: C lostridioides difficile is a major cause of infectious nosocomial diarrhea in high-income countries (1). Disease severity ranges from asymptomatic colonization to fulminant colitis, sometimes leading to colectomy and death (2). Healthcare costs attributed to C. difficile infection (CDI) are estimated to be $4.8 billion in the United States and €3 billion in Europe (3). A study in Canada estimated 38,000 annual CDI cases and conservative estimated costs of CDN $280 million resulting from extended hospital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…6,16 Canadian estimates showed an increase in ribotype 106 from 7.3% in 2015 to 18.9% in 2019. 13 Similar trends were observed in Europe based on 2016-2017 surveillance data, with a decline in ribotype 027 and the most frequent ribotype observed was 014/020. 19 In Australia, recent data between 2013 and 2018 showed ribotype 014/020 is also the most frequent strain detected.…”
Section: Incidence and Healthcare Burdensupporting
confidence: 72%
See 2 more Smart Citations
“…6,16 Canadian estimates showed an increase in ribotype 106 from 7.3% in 2015 to 18.9% in 2019. 13 Similar trends were observed in Europe based on 2016-2017 surveillance data, with a decline in ribotype 027 and the most frequent ribotype observed was 014/020. 19 In Australia, recent data between 2013 and 2018 showed ribotype 014/020 is also the most frequent strain detected.…”
Section: Incidence and Healthcare Burdensupporting
confidence: 72%
“…13 The estimated hospital-associated CDI rates in Canada decreased from 4.74 to 3.61 cases per 10,000 patient days during this period. 13 In contrast, the average annual rate of hospital-associated CDI in Australia has increased from 3.94 to 4.05 per 10,000 patient bed days between 2013 and 2018. 14 Among Asian countries, a systematic review and meta-analysis found an overall incidence in Asia that was similar to Western nations, with approximately 5.3 CDI cases per 10,000 patient days.…”
Section: Incidence and Healthcare Burdenmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous surveillance data showed a steady decline in CDI rates before the pandemic. 7,8 However, during the pandemic, we observed an increase in HA- and CA-CDI rates, whereas other jurisdictions reported varying changes in healthcare-associated infections. 9 CDI and COVID-19 coinfection was uncommon (5%); however, COVID-19 patients were more likely to be associated with HA-CDI acquisition than non–COVID-19 patients.…”
Section: Discussionmentioning
confidence: 59%
“…Clostridioides difcile (formerly Clostridium difcile) is the most common cause of hospital-associated diarrheal infections [1]. Pathogenic strains produce toxin A, B, or a binary toxin upon colonization of the gut, which can lead to a range of symptoms from diarrhea, colitis, and in severe cases death [2]. Clostridioides difcile infection (CDI) has traditionally been characterized as nosocomial, or healthcare-associated (HA), with the incidence of HA-CDI being 2.1/10 000 to 6.5/10 000 inpatient days [3].…”
Section: Introductionmentioning
confidence: 99%